KERANGKA KERJA SUSTAINABLE SUPPLY CHAIN RISK MANAGEMENT INDUSTRI KELAPA SAWIT DI INDONESIA - Rangga Primadasa (Journal of Industrial Engineering and Technology, 2020)
Abstract This paper combines three main concept including supply chain management, sustainability and risk management which is put palm oil Industry in Indonesia as an object. It explores sustainability-related supply chain risk from principle and criteria of roundtable sustainable palm oil (RSPO) and Indonesian sustainable palm oil (ISPO), distinguishes them from common supply chain risks and develop framework for their management. 45 risks across the three main pillars of sustainability (environmental, social, economic/financial) are identified from extensive review from principle and criteria of RSPO and ISPO. The fuzzy failure mode and effect analysis (fuzzy FMEA) approach is utilized to assess the relative importance of 45 risks. Based on the findings of the study, risks response and treatments are proposed for each sustainability-related supply chain risks. The findings show generally three most important risks are low OER (oil extraction rate), FFB (fresh fruit bunch) looting, un-fulfill palm oil mill capacity, respectively. Finally, integrated sustainable supply chain risk management approaches need to implement by the management of palm oil industry.